Gang entry and exit in Cape Town : getting beyond the streets in Africa's deadliest city - Dziewanski, Dariusz (Emerald Publishing Limited, 2021)
Gang violence is a concern being debated by academics, politicians, and communities around the world. Yet effective solutions are still in short supply, partly because too little research concentrates on understanding how people can escape the trap of violent street culture. Responding to that need, this book provides a detailed qualitative account of what it is like to join and then disengage from gangs in Africa's deadliest city. Through the life histories of twenty-four former Capetonian gang members, alongside hundreds of hours of additional interviews and observation from five years of ethnographic research, Dariusz Dziewanski reimagines gangsterism in a way that pays heed to the overwhelming force of street culture, but also confirms the possibility of overcoming crime and violence amid disenfranchisement and disadvantage. Rather than simply reproducing the poverty-crime-violence narrative, this book demonstrates how gang members can - and have - transformed their lives, challenging the pessimistic conclusions commonly associated with gang entry; even gang scholars studying street culture usually portray the end point to gang life as either prison or a body bag. By presenting evidence about successful gang exit, Dziewanski showcases a practical starting point for changing how criminologists think about gangs and street culture - offering hope to those trying exit gang life, as well as those trying to help them do so.